Safety and efficacy of aripiprazole for the treatment of pediatric Tourette syndrome and other chronic tic disorders - Cox JH; Seri S; Cavanna AE (Dove Medical Press, 2016)
Joanna H Cox,1 Stefano Seri,2,3 Andrea E Cavanna,2,4,5 1Heart of England NHS Foundation Trust, 2School of Life and Health Sciences, Aston Brain Centre, Aston University, 3Children’s Epilepsy Surgery Programme, The Birmingham Children’s Hospital NHS Foundation Trust, 4Department of Neuropsychiatry, Birmingham and Solihull Mental Health NHS Foundation Trust, Birmingham, 5Sobell Department of Motor Neuroscience and Movement Disorders, Institute of Neurology and UCL, London, UK Abstract: Tourette syndrome is a childhood-onset chronic tic disorder characterized by multiple motor and vocal tics and often accompanied by specific behavioral symptoms ranging from obsessionality to impulsivity. A considerable proportion of patients report significant impairment in health-related quality of life caused by the severity of their tics and behavioral symptoms and require medical intervention. The most commonly used medications are antidopaminergic agents, which have been consistently shown to be effective for tic control, but are also associated with poor tolerability because of their adverse effects. The newer antipsychotic medication aripiprazole is characterized by a unique mechanism of action (D2 partial agonism), and over the last decade has increasingly been used for the treatment of tics. We conducted a systematic literature review to assess the available evidence on the efficacy and safety of aripiprazole in pediatric patients with Tourette syndrome and other chronic tic disorders (age range: 4–18 years). Our search identified two randomized controlled trials (involving 60 and 61 participants) and ten open-label studies (involving between six and 81 participants). The majority of these studies used two validated clinician-rated instruments (Yale Global Tic Severity Scale and Clinical Global Impression scale) as primary outcome measures. The combined results from randomized controlled trials and open-label studies showed that aripiprazole is an effective, safe, and well-tolerated medication for the treatment of tics. Aripiprazole-related adverse effects (nausea, sedation, and weight gain) were less frequent compared to other antidopaminergic medications used for tic management and, when present, were mostly transient and mild. The reviewed studies were conducted on small samples and had relatively short follow-up periods, thus highlighting a need for further trials to assess the long-term use of aripiprazole in pediatric patients with Tourette syndrome and other chronic tic disorders with measurement of its efficacy using both clinician-rated and self-report scales. Keywords: Tourette syndrome, tics, aripiprazole, efficacy, tolerability